2021
DOI: 10.3389/fonc.2020.604213
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Microenvironment and Angiogenesis in Melanoma Brain Metastases

Abstract: BackgroundHigh tumor-infiltrating lymphocytes (TILs) and hemorrhage are important prognostic factors in patients who have undergone craniotomy for melanoma brain metastases (MBM) before 2011 at the University of Pittsburgh Medical Center (UPMC). We have investigated the prognostic or predictive role of these histopathologic factors in a more contemporary craniotomy cohort from the University of North Carolina at Chapel Hill (UNC-CH). We have also sought to understand better how various immune cell subsets, ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…This analysis showed that melanoma brain metastases are characterized by (a) decreased immune infiltration and (b) increased expression of genes in the metabolic pathway of oxidative phosphorylation (OXPHOS). The observed decrease in T‐cell infiltration was consistent with previous characterization of melanoma brain metastases by other methods 67,68 and may contribute to the decreased clinical activity of anti‐PD1 immunotherapy in patients with CNS metastases. The increase in expression of OXPHOS genes in the clinical brain metastases was recapitulated by directly injecting human melanoma cells into brain tissue (compared with subcutaneous injection), strongly supporting that this phenomenon is induced by the brain TME.…”
Section: Position: Rationale For Early‐phase Trials Specifically For Patients With Brain Metastasessupporting
confidence: 89%
“…This analysis showed that melanoma brain metastases are characterized by (a) decreased immune infiltration and (b) increased expression of genes in the metabolic pathway of oxidative phosphorylation (OXPHOS). The observed decrease in T‐cell infiltration was consistent with previous characterization of melanoma brain metastases by other methods 67,68 and may contribute to the decreased clinical activity of anti‐PD1 immunotherapy in patients with CNS metastases. The increase in expression of OXPHOS genes in the clinical brain metastases was recapitulated by directly injecting human melanoma cells into brain tissue (compared with subcutaneous injection), strongly supporting that this phenomenon is induced by the brain TME.…”
Section: Position: Rationale For Early‐phase Trials Specifically For Patients With Brain Metastasessupporting
confidence: 89%
“…We analyzed the expression of β-catenin across different cellular compartments within the brain (i.e., melanoma, reactive glia, TILs, normal brain parenchyma) using the Wilcoxon matched-pairs signed-rank test, as we have previously described [26]. We investigated the correlation between protein expression of various proteins by melanoma cells and TIL density using the Kendall rank correlation statistic.…”
Section: Discussionmentioning
confidence: 99%
“…We dichotomized protein expression of β-catenin in melanoma cells by IHC as high expression (2+, 3+) or low/absent expression (0, 1+) by IHC. We then performed an OS analysis to assess the prognostic significance of β-catenin in MBM using the Kaplan-Meier method, as we have previously described [26]. We performed statistical analysis using Prism 8 (GraphPad Software, version 8.3.1, San Diego CA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations